Mopo’alati Tradition In The Coastal Muslim Community At Molotabu Beach Bone Bolango District - Rahmawati Rahmawati; Kasim Yahiji; Muh Rusli (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2019)
This paper elaborates on the reality of the Mopo'alati tradition in Gorontalo. It expresses respect, hopes to the sacred, and supernatural. This tradition is celebrated once a year in the month of Muharram by Muslim communities on the coast of Molotabu as an expression of gratitude and prayer of salvation in facing a hard life and challenging sea. The study used a qualitative descriptive method through ethnographic design in order to understand deeply the philosophy of the tradition and its correlation with world life. Mopo’alati tradition is urgent to be studied in order to identify the inconsistency values deviates from Islam and encouraged the ritual ceremony to Islamic nuance. The finding illustrates that Gorontalo society is very fanatical about Islam, thus all mental-spiritual activities, social activities, and traditions must be based on the philosophy of “Adati hulo huloa to Syara’ah, Syara’ah hula hula’a to Qur’ani”. It means the custom bases on religious values and the religious values base on Alquran. This philosophy contains the very deep meaning of tauhid (God's values). On another side, Gorontalo society defenced the ancestor's tradition even though it deviated from Islamic values. Nowadays, Mopo’alati tradition is packaged in a ritual format by giving a more objective moral light. The ceremony was started by doing two rakaat of unobligation pray, reciting al-Waqi’ah verse, al-Rahman verse, and Yasin verse, reciting zikir, and closed by reciting safety pray. Mopo’alati ceremony was closed by giving food, cakes, and money which collected in a ceremony to poor people around the village.